2009
DOI: 10.1002/adsc.200900628
|View full text |Cite
|
Sign up to set email alerts
|

Facile Synthesis of Enantiopure 4‐Substituted 2‐Hydroxy‐4‐ butyrolactones using a Robust Fusarium Lactonase

Abstract: A facile chemo-enzymatic process has been developed for producing stereoisomers of 4-substituted 2-hydroxy-4-butyrolactones with good to excellent enantioselectivity. This process involves an easy separation of the diastereoisomers by column chromatography and efficient enzymatic resolution by whole cells of Escherichia coli JM109 expressing Fusarium proliferatum lactonase gene. This biocatalyst shows strong tolerance towards different substrate structures and at least three out four possible isomers could be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 40 publications
(23 reference statements)
0
9
0
Order By: Relevance
“…As SnCl 4 ·5H 2 Ow as the most suitable homogeneous catalyst in the experiments discussed above, it was also employed as ac atalyst in this part of the study.T he benzaldehyde derivatives 1-naphthaldehyde (2b), 2-naphthaldehyde (2c), and 4-phenylbenzaldehyde (2d) led to 3b, 3c,a nd 3d,w ith yields of 26 %, 30 %, and3 1%,r espectively.O nt he other hand, o-, m-, and p-substituted chlorobenzaldehyde 2f, 2g, 2h led to 3f, 3g,a nd 3h,w ith yields of 34 %, 32 %, and 31 %, respectively.T he use of benzaldehyde derivatives thus led to the highest selectivity in the transformation to the desired coupling products.T hese results show that the sterich indrance and the substituent position do not affect the reactive performance of the aldehydes ource;h owever,t he reactionc arried out with anisaldehyde (2e)d id not yield the desired product 3e.F inally,u sing propionaldehyde (2i)a nd enanthaldehyde (2j)a lkylaldehyde derivatives resulted in 3i [9] 4 2 < 1--7S nI 2 2133 73:27 8S nI 4 1 Chem. Asian J.…”
Section: Resultsmentioning
confidence: 99%
“…As SnCl 4 ·5H 2 Ow as the most suitable homogeneous catalyst in the experiments discussed above, it was also employed as ac atalyst in this part of the study.T he benzaldehyde derivatives 1-naphthaldehyde (2b), 2-naphthaldehyde (2c), and 4-phenylbenzaldehyde (2d) led to 3b, 3c,a nd 3d,w ith yields of 26 %, 30 %, and3 1%,r espectively.O nt he other hand, o-, m-, and p-substituted chlorobenzaldehyde 2f, 2g, 2h led to 3f, 3g,a nd 3h,w ith yields of 34 %, 32 %, and 31 %, respectively.T he use of benzaldehyde derivatives thus led to the highest selectivity in the transformation to the desired coupling products.T hese results show that the sterich indrance and the substituent position do not affect the reactive performance of the aldehydes ource;h owever,t he reactionc arried out with anisaldehyde (2e)d id not yield the desired product 3e.F inally,u sing propionaldehyde (2i)a nd enanthaldehyde (2j)a lkylaldehyde derivatives resulted in 3i [9] 4 2 < 1--7S nI 2 2133 73:27 8S nI 4 1 Chem. Asian J.…”
Section: Resultsmentioning
confidence: 99%
“…As mentioned above, 5-membered lactones are useful not only as fine chemicals but also as raw materials. In particular, 5-membered lactones possessing a hydroxyl group in the α-position are also attractive synthetic targets, with the majority of chemical [34,35,36,37,38,39,40,41,42,43,44,45] or enzymatic [46,47,48] syntheses being based on multistep processes. For example, Kagayama et al reported the multi-step synthesis of α-hydroxy-γ-butyrolactone (HBL), one of the simplest 5-membered lactones, from 1,3-dioxorane and methyl acrylate, which are relatively cheap commercially available compounds, in the presence of an N -hydroxyphthalimide (NHPI) catalyst (Scheme 9) [37].…”
Section: Cascade Synthesis Of Useful Four-carbon Products Via An Imentioning
confidence: 99%
“…For related structures, see: Becerra et al (2010); Liu et al (2008); Nair, Devipriya & Eringathodi (2007) ;Nair, Vellalath et al (2007); Bushueva et al (2010). For background information on applications, see: Atalar et al (2009); Chen et al (2009); Charati et al (2008); Cao et al (2008); Wu et al (2008). For the synthetic procedure, see: Schweiger et al (2000).…”
Section: Related Literaturementioning
confidence: 99%
“…Data collection: SMART (Bruker, 2007); cell refinement: SAINT (Bruker, 2007); data reduction: SAINT; program(s) used to solve structure: SHELXS97 (Sheldrick, 2008); program(s) used to refine structure: SHELXL97 (Sheldrick, 2008); molecular graphics: SHELXTL (Sheldrick, 2008); software used to prepare material for publication: SHELXTL. Electroactive and photoactive thiophene-based molecules, oligomers, and polymers (Atalar et al, 2009;Chen et al, 2009;Charati et al, 2008;Becerra et al, 2010;Liu et al, 2008;Nair, Devipriya & Eringathodi, 2007;Nair, Vellalath et al, 2007;Bushueva et al; are important for advanced technological applications, including display technologies, field-effect transistors, solar cells, sensors, nonlinear optics, molecular wires, and diodes (Cao et al, 2008;Wu et al, 2008). Thiophenes and its derivatives are originally applied to synthesize thiophene-based compounds, such as, oligomers and polythiophenes due to easy electropolymerization of thiophenes to produce stable, electrically conductive polymeric films.…”
Section: Data Collectionmentioning
confidence: 99%